Knowing the epidemic is the best way to define diagnosis and treatment strategies to reach the 90-90-90 goals: the experience of Portugal in using the ECDC HIV modelling tool - Diniz, António (2017)
Introduction: In Portugal, data from the continuous of care show that in 2014 approximately 34,000 persons living with HIV (PLHIV) were in care, 82.8% of which on antiretroviral treatment and 78.4% virologically suppressed. However, updated estimates for HIV prevalence, incidence and PLHIV diagnosed are still missing, making difficult defining appropriate diagnosis and treatment strategies to reach the 90–90–90 goals.